Exogenous fibroblast growth factor 1 ameliorates diabetes-induced cognitive decline via coordinately regulating PI3K/AKT signaling and PERK signaling - Wu, Yanqing (Cell Commun Signal, 2020)
BACKGROUND: Diabetes induces central nervous system damage, leading to cognitive decline. Fibroblast growth factor 1 (FGF1) has dual function of neuroprotection and normalizing hyperglycemia. To date, the precise mechanisms and potential treating strategies of FGF1 for diabetes-induced cognitive decline (DICD) hasn’t been fully elucidated. METHODS: In this study, db/db mice were used as DICD animal model. We found that diabetes remarkably suppressed FGF1 expression in hippocampus. Thus, exogenous FGF1 had been treated for db/db mice and SH-SY5Y cells. RESULTS: FGF1 significantly ameliorates DICD with better spatial learning and memory function. Moreover, FGF1 blocked diabetes-induced morphological structure change, neuronal apoptosis and Aβ(1–42) deposition and synaptic dysfunction in hippocampus. But normalizing glucose may not the only contributed factor for FGF1 treating DICD with evidencing that metformin-treated db/db mice has a inferior cognitive function than that in FGF1 group. Current mechanistic study had found that diabetes inhibits cAMP-response element binding protein (CREB) activity and subsequently suppresses brain derived neurotrophic factor (BDNF) level via coordinately regulating PERK signaling and PI3K/AKT signaling in hippocampus, which were reversed by FGF1. CONCLUSION: We conclude that FGF1 exerts its neuroprotective role and normalizing hyperglycemia effect, consequently ameliorates DICD, implying FGF1 holds a great promise to develop a new treatment for DICD.